Analysis of low-energy and high-frequency femtosecond laser for the construction of deep anterior donor corneal lamellae - Victor,Gustavo (2014)
Purpose: To evaluate the efficacy and reliability of a low-energy femtosecond laser with a high repetition rate for construction of deep anterior donor corneal lamellae. Methods: This was a prospective laboratory investigation. Twenty-five human corneal buttons were femtosecond laser cut to create thick anterior lamellae (diameter, 10mm; thickness, 500µm). The laser cuts were made using an LDV® femtosecond laser in a Ziemer® anterior chamber. To obtain a better edge, the lamellae were trephined with an 8mm trephine (Katena®). The central corneal thickness and the anterior lamellae were measured using a Mitutoyo® thickness gauge with an accuracy of 0.001mm. Results: The central thickness of the 25 corneas ranged from 500 to 705µm (mean, 584 ± 51µm). The thickness of the anterior lamellae ranged from 420 to 480µm (mean, 455 ± 12.7µm). The anterior lamellae diameters were 7.90 ± 0.1mm, and all laser cuts were round. The lamellar interfaces appeared regular by surgical microscopy. There were no cases of inter-lamellar adhesion. Conclusion: The LDV® femtosecond laser appears to be a safe and reliable instrument for cutting deep anterior lamellae from donor corneoscleral buttons. Minimal variation in donor lamellar depth with the laser will be useful for creating donor corneal tissue for deeper anterior lamellar keratoplasty or endothelial keratoplasty surgery or both from a single donor cornea.